Development of a Tool to Perform Vehicle Road Tests - Silva, Manuel Gameiro; Gültekin, Ahmet; Ãœnlütürk, Eren (International Journal of Interactive Mobile Technologies (iJIM), 2017)
The development of a tool to analyse data collected in car road tests is presented, allowing a better understanding of the Physics of car motion. Using the measured data of fuel consumption and the main variables related to the vehicle displacement, it is possible to make corrections to the influence of the main disturbing factors and clearly improve the quality of road tests based evaluations. Thus, the fuel consumption rate is continuously recorded during the motion of the vehicle, whereas the power required to ensure displacement can be calculated using a simulation model with the data recorded during a path. Integrating over time the average power values at each interval, the energy necessary to ensure the vehicle displacement is calculated, while integrating the fuel rate over the duration of the path, the fuel consumption is computed. The ratio between the theoretically required energy and the one actually spent provides the conversion efficiency of the vehicle propulsion system. The developed tool is very useful in the framework of the courses about car dynamics included in Mechanical or Automotive Engineering Programmes. The developed tool couples data collected during road tests with a simulation model that computes all the force components acting on the car body during the motion. It has been written in LabView and an attractive graphical interface is used to keep the attention of the students when the data is displayed in real-time or analysed based upon previously recorded files.